Harvesting energy from planetary gear using piezoelectric material - Chilabi, Haider Jaafar; Salleh, Hanim; Supeni, Eris Elianddy; As'arry, Azizan; Md Rezali, Khairil Anas; Atrah, Ahmed B. (MDPI, 2020)
In the present study, a rotational piezoelectric (PZT) energy harvester has been designed, fabricated and tested. The design can enhance output power by frequency up-conversion and provide the desired output power range from a fixed input rotational speed by increasing the interchangeable planet cover numbers which is the novelty of this work. The prototype ability to harvest energy has been evaluated with four experiments, which determine the effect of rotational speed, interchangeable planet cover numbers, the distance between PZTs, and PZTs numbers. Increasing rotational speed shows that it can increase output power. However, increasing planet cover numbers can increase the output power without the need to increase speed or any excitation element. With the usage of one, two, and four planet cover numbers, the prototype is able to harvest output power of 0.414 mW, 0.672 mW, and 1.566 mW, respectively, at 50 kΩ with 1500 rpm, and 6.25 Hz bending frequency of the PZT. Moreover, when three cantilevers are used with 35 kΩ loads, the output power is 6.007 mW, and the power density of piezoelectric material is 9.59 mW/cm3. It was concluded that the model could work for frequency up-conversion and provide the desired output power range from a fixed input rotational speed and may result in a longer lifetime of the PZT.